Perceived stress among university students in UUM during COVID-19-induced online learning - Sriletcumy Maran, Maran (2022)
Covid-19 is discovered infectious Coronavirus that became pandemic. Since disease outbreaks can have mental health consequences, this study examine how university students' views of UUM undergraduate students' stress were affected by Covid-19- induced e-learning. The objectives of study to examine the perceived stress of undergraduates in UUM due to the implementation of online class. A survey was distributed through online questionnaire focuses on UUM Sintok university students in Kedah. A total of 163 data was collected and used for analyses purpose. The findings of this study shows that students experienced high-moderate stress. The limitation and recommendations for future studies were further discussed.